A study about the use of Musicomovigrams in musical education - Rubio, Miguel Clemente; Fornari Junior, José; Mendes, Adriana N. (Revista Vórtex, 2017)
Since the turn of the twenty-first century, information and communication technology (ICT) have definitely changed the way people express learning and interact with each other in the activities of science and arts, with a particular impact in musical education. In this article, the authors treat the concept of musicomovigrams, an interactive audiovisual resource, similar to video games that can work as software tools for the development of sound perception and musical structure. This concept is based on the previous concept of musicogram, created by the musical pedagogue Jos Wuytack along with his concept of Active Listening (Wuytack and Boal Palheiros, 2009). The authors consider an important element of learning the concepts of Musical Forms defined by the musical educator Keith Swanwick (Swanwick, 2003). This work presents the development of the musicomovigram concept, a videogame created through the free software eAdventure. We also intend to investigate how music teachers and students, who work and interact in musical education classrooms, are actually accepting and using ICT in their classes.